Methodological issues in consciousness research: theory comparison, the role of empirical evidence, and a replication crisis - Kirkeby-Hinrup, Asger; Stephens, Andreas; Balogh Sjöstrand, Aron; Overgaard, Morten (Frontiers in Psychology, 2025)
Which of the many available theories of consciousness should a newcomer to the field choose? We consider possible ways to deal with this conundrum. We argue that convergence of theories is unlikely. Next, we consider ways comparing theories highlighting significant issues with existing endeavors in this regard. Given the nature of the field, presumably empirical support has a critical role to play when assessing theories. We examine a selection of hot topics—widely debated cases—and conclude that despite these supposedly exemplifying the best possible conditions for progress, they all struggle to move forward debates between theories. This leaves the large amounts of proposed evidence that never became hot topics, the so-called cold cases as a candidate to guide us in the conundrum. However, the lack of insight into the number of these and the lack of quality control as to whether each was in fact applicable to any given theory, is akin to a replication crisis. Irrespective of the conundrum, this looms large over any attempt to assess and compare theories according to empirical plausibility. There is a simple remedy for this: reduce the number of cold cases through independent assessment. Finally, we explore if a way out of the conundrum is to reject the need to choose between theories and consider proposals that reject the “theory-based” approach to consciousness studies.